Development of Environmentally Friedly Fabrics and Their Use for Personal Protective Equipment - Sadikov, A. I.; Khamidullaev, F.; Yuldasheva, O. M. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides information on obtaining environmentally friendly textile fabrics and their use for personal protective equipment.